PROBLEM DAN IMPLEMENTASI PELEDAKAN PENDUDUK LANSIA MENJELANG TAHUN 2020 - Romziah S. B. (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1996)
Indonesia's fertility rate has continued to decline, it dropped to 2.87 at the end of the long term development plan period. Thisfertility rate is projected to go down by 40 percent in the period 1990-2020. However, the life expectancy will increase to 17 percent. This therefore, means that the decline of the totalfertility rate in Indonesia is faster than the rate of increase of the life expectancy rate.A vital transition in Indonesia will have an affect the number of the elderly people at least upto the year 2020. There will be 28.8 million elderly people or 11.3 percent of the nation's population. Hence, the structure and composition of Indonesia's population will be significantly changed.With the higher level of migration and increasing participation of females in the workforce, chances that an elderly person will have a child living close - by is being reduced, also and the availability of caregivers in thefamily house is also declining. There are few problems facing care for the aged in Indonesia such as: low priority, inadequate information on the elderly, poor facilities and infrastructure, lack of essential personnel, spiraling medical cost, changing epidemiological pattern of disease, lack of resources, inadequate family support, insufficient operations research.To improve on care for the elderly, the following need to be implemented: improved political commitment and the coverageof health service and or social services for the elderly, developing the relevant manpower to work with the elderly, identifying and mobilizingadequate resources to cover care for the aged.